Changing morbidity-free life expectancy in India by gender and place of residence - Shabnam, Shewli (International Journal Of Community Medicine And Public Health, 2023)
Background: With declining fertility and increasing life expectancy, India faces a growing burden of chronic diseases. Therefore, research in morbidity-free life expectancies (MFLE) is gaining importance in India. This study explores the changes in MFLE among males and females and rural and urban residents in India between 2004 and 2017-18. Methods: The Sullivan method was used for estimating MFLE. Age-specific morbidity rates were computed from the 60th and the 75th round of the National Sample Survey (NSS) data. The information on mortality was collected from the Sample Registration System life tables of India for the periods 2002-06 and 2014-18. Results: In India, the morbidity-free life expectancy of both genders improved between 2004 and 2017-18, except for the population 80 years and above. Life expectancy (LE) and MFLE were higher among women in India, but the proportion of MFLE to total LE was higher among men in most age groups in 2004 and 2017-18. This contradiction is known as the gender health paradox. The study found that LE was higher in urban areas, but MFLE was lower among the urban population except for infancy and early childhood. Conclusions: The gender health paradox prevails in India for most age groups. As the proportion of MFLE to total LE can be viewed as an indicator of the quality of life, it is crucial to set the target of lowering the morbidity rates among women and the urban population.